2013
DOI: 10.1108/ijshe-06-2011-0044
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable consumption: a teaching intervention in higher education

Abstract: Purpose – The purpose of this paper is to describe and analyse a teaching strategy designed to increase the awareness of trainee teachers and educate them with regard to sustainable consumption. Design/methodology/approach – Ninety-four subjects (trainee teachers) were assessed on their knowledge of the environmental impacts of consumerism, their attitudes to sustainable consumption and their behavioural intentions before (pre-test) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Several authors have pointed out the lack of awareness about the connections between individual decisions and behaviours and certain socio-ecological problems, such as BD loss [3,21,25]. For their part, Yli-Panula et al [18] found that many Nordic student teachers did not understand that the actions of human beings lead to BD loss.…”
Section: The Close Relationship Between Our Lifestyle and Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have pointed out the lack of awareness about the connections between individual decisions and behaviours and certain socio-ecological problems, such as BD loss [3,21,25]. For their part, Yli-Panula et al [18] found that many Nordic student teachers did not understand that the actions of human beings lead to BD loss.…”
Section: The Close Relationship Between Our Lifestyle and Sustainabilitymentioning
confidence: 99%
“…For their part, Yli-Panula et al [18] found that many Nordic student teachers did not understand that the actions of human beings lead to BD loss. Regarding this problem, the assessment of the initial ideas of Spanish pre-service teachers also revealed a lack of knowledge about the causes and consequences of the problem [25]. Thus, it is still a challenge for the society and pre-service teachers, in particular, to build strong relationships between sustainability and our lifestyle.…”
Section: The Close Relationship Between Our Lifestyle and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bissonette and Contento (2001) proposed that, especially when working with adolescents, one needs to make the impact of environment-unfriendly practices more salient for them through cognitive and experiential approaches. Álvarez-Suárez et al (2014) used the classroom as a community setting where the first step was to identify obstacles to environmentally-friendly behavior, followed by Table 2 Key messages from selected guidance instruments promoting sustainable diets Adapted from Piscopo (2013: 86-87) • Favour a plant-based diet which incorporates a variety of foods, ranging from grains, to v egetables, pulses, fruit, nuts and herbs and spices • Frequently consume raw vegetables and fruit • Opt for 'whole' varieties of grains • Opt for foods which have been cultivated or reared organically, are in season and are produced locally • If consumed, eat meat (including processed) and fish and seafood only a few times a week and avoid large portion sizes of meat • Keep foods high in less healthy fats and/or sugars to a minimum • Drink local tap water and local fresh fruit juices more than bottled water and sweetened soft drinks • Seek eco-friendly labelling, such as organically-farmed, non-GMO and sustainably-fished food certification, recyclable packaging symbols the design of small-group behaviour modification strategies that could then be extended to the community at large. This thinking is in keeping with argument that Education for Sustainable Consumption could benefit from the application of social learning theory through observational learning and as part of authentic consumer education curricula.…”
Section: Sustainable Food Consumptionmentioning
confidence: 99%
“…Such engagement should begin early in the planning stages, to generate meaningful and inclusive public input on planned science communication efforts [19]. In addition, new approaches should consider ways to empower the public to act, moving beyond the perceived helplessness often felt in the face of complex sustainability problems [20].…”
Section: Introductionmentioning
confidence: 99%